Sub-regional snow cover distribution across the southern Appalachian Mountains. (4th March 2017) - Sugg, Johnathan W.; Fuhrmann, Christopher M.; Perry, L. Baker; Hall, Dorothy K.; Konrad, Charles E.
Abstract: Snowfall in the Southern Appalachian Mountain region of the eastern US is characterized by much spatiotemporal variability. Annual snowfall totals vary by up to 75 cm, and variations in snowfall intensity can lead to large differences in the local snowfall distribution. Research has shown that the synoptic pattern associated with the snowfall strongly influences the regional-scale distribution of snow cover. However, topographic variability results in locally complex snow cover patterns that are not well understood or documented. In this study, we characterize the snow covered area (SCA) and fractional snow cover associated with different synoptic patterns in 14 individual sub-regions. We analyze 63 snow events using Moderate-resolution Imaging Spectroradiometer standard snow cover products to ascertain both qualitative and quantitative differences in snow cover across sub-regions. Among sub-regions, there is significant variation in the snow cover pattern from individual synoptic classes. Furthermore, the percent SCA follows the regional snowfall climatology, and sub-regions with the highest elevations and northerly latitudes exhibit the greatest variability. Results of the sub-regional analysis provide valuable guidance to forecasters by contributing a deeper understanding of local snow cover patterns and their relationship to synoptic-scale circulation features.